(Still) longing for food: Insulin reactivity modulates response to food pictures. Issue 10 (28th March 2012) - Kroemer, Nils B.; Krebs, Lena; Kobiella, Andrea; Grimm, Oliver; Vollstädt‐Klein, Sabine; Wolfensteller, Uta; Kling, Ricarda; Bidlingmaier, Martin; Zimmermann, Ulrich S.; Smolka, Michael N.
<x xml:space="preserve">Abstract</x> Overweight and obesity pose serious challenges to public health and are promoted by our food‐rich environment. We used functional magnetic resonance imaging (fMRI) to investigate reactivity to food cues after overnight fasting and following a standardized caloric intake (i.e., a 75 g oral glucose tolerance test, OGTT) in 26 participants (body mass index, BMI between 18.5 and 24.9 kg m−2). They viewed pictures of palatable food and low‐level control stimuli in a block design and rated their current appetite after each block. Compared to control pictures, food pictures activated a large bilateral network typically involved in homeostatically and hedonically motivated food processing. Glucose ingestion was followed by decreased activation in the basal ganglia and paralimbic regions and increased activation in parietal and occipital regions. Plasma level increases in insulin correlated with cue‐induced appetite at the neural and behavioral level. High insulin increases were associated with reduced activation in various bilateral regions including the fusiform gyrus, the superior temporal gyrus, the medial frontal gyrus, and the limbic system in the right hemisphere. In addition, they were accompanied by lower subjective appetite ratings following food pictures and modulated the neural response associated with it (e.g., in the fusiform gyrus). We conclude that individual insulin reactivity is critical to reduce food‐cue responsivity after an initial energy intake and thereby may help to counteract overeating. Hum Brain Mapp 34:2367–2380, 2013. © 2012 Wiley Periodicals, Inc.